Dielectric relaxation in Se₈₀Ge₂₀ and Se₇₅Ge₂₀Ag₅ chalcogenide glasses - Dwivedi, A.; Arora, R.; Mehta, N.; Choudhary, N.; Kumar, A. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2005)
Temperature and frequency dependence of dielectric constant (ε') and dielectric loss (ε") are studied in glassy Se₈₀Ge₂₀ and Se₇₅Ge₂₀Ag₅. The measurements have been made in the frequency range (1 to 10 kHz) and in the temperature range 300 to 395 K. No dielectric dispersion is observed in glassy Se80Ge20. However, the results indicate that the dielectric dispersion exists in Se₇₅Ge₂₀Ag₅ in the above frequency and temperature range. An analysis of the dielectric loss data shows that the Guintini theory of dielectric dispersion based on two electron hopping over a potential barrier is applicable in the present case.